Outcomes of Localized Esophageal Squamous Cell Carcinoma Patients Treated With Definitive Concurrent Chemoradiotherapy Using Either Standard or High Radiotherapy Dose: A Retrospective Study Controlling for Organ at Risk Dose - LI, CHIA-CHIN; FANG, HSIN-YUAN; LIN, CHEN-YUAN; SHEN, WEI-CHIH; CHIEN, CHUN-RU (Anticancer research, 2019)
The optimal radiotherapy dose for localized esophageal squamous cell carcinoma (ESqCC) patients treated with definitive concurrent chemo-radiotherapy (CCRT) is debated. The aim of our study was to compare patient outcomes using either standard or high radiotherapy dose. Eligible patients diagnosed between 2011 and 2015 from the cancer registry of our Institute were identified and a propensity score (PS)-matched cohort (1:1 for high vs. standard dose) was constructed to balance observable potential confounders (including organ at risk dose). The hazard ratio (HR) of death between high and standard dose was compared. Our study population included 73/36 patients before/after PS matching. The HR of death at the high dose compared to the standard dose was 0.554 (95% confidence interval (CI)=0.308-0.998, p=0.049). Definitive CCRT using a high radiotherapy dose showed improved survival outcomes for localized ESqCC patients compared to standard dose.